2014
DOI: 10.1152/japplphysiol.00121.2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogen on skeletal muscle mitochondrial function in ovariectomized rats: a time course study in different fiber types

Abstract: Postmenopausal women are prone to develop obesity and insulin resistance, which might be related to skeletal muscle mitochondrial dysfunction. In a rat model of ovariectomy (OVX), skeletal muscle mitochondrial function was examined at short- and long-term periods after castration. Mitochondrial parameters in the soleus and white gastrocnemius muscle fibers were analyzed. Three weeks after surgery, there were no differences in coupled mitochondrial respiration (ATP synthesis) with pyruvate, malate, and succinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 59 publications
10
72
1
Order By: Relevance
“…33,34 Impairment in skeletal muscle mitochondrial content and oxidation after ovariectomy in rodents further suggest a role for estrogens. 35 Importantly, recent studies of muscle-specific ERα knockout (αMERKO) mice demonstrated a role for skeletal muscle ERα on mitochondrial function and metabolic homeostasis. 16 The impaired glucose homeostasis observed in the αMERKO mice was paralleled by abnormal mitochondrial morphology, impaired mitochondrial fission dynamics, and overexpression of reactive oxygen species in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Impairment in skeletal muscle mitochondrial content and oxidation after ovariectomy in rodents further suggest a role for estrogens. 35 Importantly, recent studies of muscle-specific ERα knockout (αMERKO) mice demonstrated a role for skeletal muscle ERα on mitochondrial function and metabolic homeostasis. 16 The impaired glucose homeostasis observed in the αMERKO mice was paralleled by abnormal mitochondrial morphology, impaired mitochondrial fission dynamics, and overexpression of reactive oxygen species in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function and the response to oxidative stress can be strongly affected by fiber composition (Anderson & Neufer 2006, Picard et al 2008, 2012. Ovariectomy has been reported to modify muscle contractile properties, phenotype, metabolism, and force-generating capacity (Moran et al 2006, Liu et al 2009c, whereas estradiol replacement reverses these alterations (Moran et al 2007, Liu et al 2009b, Cavalcanti-de-Albuquerque et al 2014. In this sense, it is not possible to rule out the hypothesis that the changes observed in white gastrocnemius mitochondrial function and oxidative stress response from OVX and OVXCE 2 rats are mediated by a change in fiber metabolism or phenotype; further studies would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of oestrogens decrease PGC1α expression indicating a putative decrease in mitochondrial biogenesis (Cavalcanti-de-Albuquerque et al, 2014).…”
Section: Do Fat Accumulation and Mitochondrial Dysfunction Depend On mentioning
confidence: 99%
“…Changes in oestrogens during ageing can also affect directly the activity of regulators of mitochondria. In rats, a model of menopause by using ovariectomization suggested that reduction of oestrogens produced the decrease of PGC1α expression and the reduction of β-oxidation in muscle (Cavalcanti-de-Albuquerque et al, 2014). This suggests that an oestrogendependent effect can induce accumulation of fat and probably insulin resistance in muscle.…”
Section: Does Fat Accumulation and Mitochondrial Dysfunction Depend Omentioning
confidence: 99%